Analisis Fikih Siyāsah terhadap Reformasi Kepolisian Negara Republik Indonesia - Raja Pagaran Harahap; Syafruddin Syam (CV Global Research Publication, 2026)
The reform of the Indonesian National Police (Polri) following the 1998 Reform era has not fully succeeded in establishing a professional, independent, and accountable law enforcement institution. Issues such as abuse of authority, weak oversight mechanisms, and potential political intervention in policing remain significant challenges to law enforcement in Indonesia. This study aims to analyze the role of the Indonesian National Police within Indonesia's constitutional system after the Reform era and to examine police reform from the perspective of fikih siyāsah. This research employs a normative legal approach with library research as the primary data collection method. The study is descriptive in nature and adopts a problem-solution approach. The findings indicate that, first, the Indonesian National Police plays a strategic role in law enforcement; however, its position directly under the President creates the potential for political intervention that may affect its institutional independence. Second, strengthening institutional oversight and supervisory mechanisms is necessary through the enhancement of existing monitoring systems and amendments to Law Number 2 of 2002 concerning the Indonesian National Police. Third, from the perspective of fikih siyāsah, the institutions comparable to the modern police are hisbah and syurṭah, which are responsible for maintaining public order, enforcing justice, and implementing the principles of al-amr bi al-ma‘rūf wa al-nahy ‘an al-munkar.